Application of Spectroscopic and Hyperspectral Imaging Techniques for Rapid and Nondestructive Investigation of Jewish Ritual Parchment - Cortea, Ioana Maria; Ghervase, Luminiţa; Ratoiu, Lucian; Rădvan, Roxana (Frontiers in Materials, 2020)
The paper presents a multi-analytical investigation of a severely degraded Jewish ritual parchment coming from a private collection. The main aim of the study was to obtain key information on the parchment manufacturing technique and original materials used, information that could help understand the historical context of the object. To this aim a series of non-invasive investigations were carried by means of multi- and hyperspectral imaging, Fourier-transform infrared (FTIR) spectroscopy and X-ray fluorescence (XRF) spectroscopy. Specific degradations as well as mapping of previous conservation treatments could be highlighted via multi-spectral imaging. Short-wave infrared images indicated the use of both iron-gall and carbon black ink, probably one related to the original writing and the other to a later intervention. To improve the imaging of degraded or partially lost text, a linear spectral unmixing classification of the HSI dataset was proposed, that showed promising results, allowing it to be applied to similar objects. XRF analysis offered an in-depth view of the chemical fingerprint of the original iron-gall ink, and critical findings on the existence of other inorganic compounds originating from the parchment manufacture. Registered FTIR data indicated denaturation of the collagen fibers, the presence of fungal-derived calcium oxalates and zinc carboxylates. In accordance with ancient Jewish parchments preparation techniques, the use of calcium sulfate, vegetable tannins and oils was also inferred from the registered infrared spectra. The corroborated results offer valuable information on the origin, production technology, and overall degradation state of the parchment manuscript. Not least, the findings could be of great interest for conservators and restorers in the field.